Reviewing existing policy and practices relating to the usage of public places in the city of Kuching South : an action research case study - Eliza, Binti Said (1998)
This study was undertaken to review existing policy and practices relating to the use of public places by traders and businesses in the City of Kuching South, with a view to making them more effective using Action Research methodology. Over the past few years, the Council of the City of Kuching South had shown much concern on the indiscriminate use of public places as extended areas for trading purposes. All over the city, items like tables and chairs, food stalls, food and/or drinks dispensing machines and motorcycles could be found placed in public places especially public walkways, pedestrian malls, back-lanes and parking places.